Comparison of Molecular and Histologic Ultrastaging Methods in Sentinel Lymph Node Analysis from Clinical Stage II Colon Cancers. Issue 7 (August 2019) - Deroo, Olivier; Lakkis, Zaher; Paquette, Brice; Grand, David; Monnien, Franck; Felix, Sophie; Borg, Christophe; Heyd, Bruno; Kim, Stefano; Valmary-Degano, Séverine
Abstract : Various studies have demonstrated that occult metastases may be present in patients with clinical stage II colon cancer. The objective of this prospective investigation was to compare the performance of molecular analysis and histologic ultrastaging in detecting occult metastases in sentinel lymph nodes (SLNs). SLNs were collected ex vivo during surgery in 29 patients. Quantitative reverse-transcription polymerase chain reaction (qRT-PCR) assays were constructed. The results were compared with histologic ultrastaging analysis by hemalum and eosin stain and immunohistochemistry on step serial sections. At least 1 SLN was identified in 76% of the cases. The first hemalum and eosin section identified metastases in 23% of the 22 SLNs. Immunohistochemistry identified isolated tumor cells in 24% of the remaining 17 cases. An overall 73% of the SLNs analyzed by qRT-PCR were positive. Four of them were negative for ultrastaging analysis. qRT-PCR is a powerful tool for the detection of occult metastases in colorectal SLN and seems to be more sensitive than histologic ultrastaging analysis. A larger prospective cohort study is necessary to provide further evidence.